FLOW IN POROUS ELEMENTS: A THEORETICAL AND EXPERIMENTAL ANALYSIS OF THE EFFECTS OF THE CAPILLARY EFFORTS CAUSED BY WATER PERCOLATION IN MASONRY POROUS ELEMENTS - França, A. C.; Carrocci, L. R. (Revista de Engenharia Térmica, 2007)
The identification of cracks in masonry bricks is quite common, not only after the edification but also during the process. Moistness absorbed by the elements of the wall (bricks and mortar) is one those factors. This moistness comes from the air, rain, soil absorption and even the excess of water in the laying mortar. In contact with the wall porous elements, the moistness will contribute to the capillary percolation, giving berth to considerable internal efforts which will induce the presence of cracks. This study leads to an analysis for the obtainment of fluid pressure and velocity medium values, measuring the deformation of the elements. The paper brings the equating to predict and estimate the velocities and efforts medium values in the ceramics elements. The flow in porous elements is studied and a proposal of modeling to estimate Velocities and Efforts values is presented.